BUXORO ARABLARI (tarixiy - etnologik tadqiqot). (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2026)
This article examines the formation of the Bukhara Arabs as an ethnic group, their migration into Transoxiana, settlement in the Bukhara oasis, and ethnocultural development processes. Special attention is paid to the interaction between Arabs and the local population, ethnic integration processes, and the demographic and ethnic situation during the period of the Emirate of Bukhara. Based on historical and ethnological sources, the study explores issues related to language, culture, and the preservation of ethnic identity among the Bukhara Arabs.